2005
DOI: 10.1177/10883576050200030401
|View full text |Cite
|
Sign up to set email alerts
|

Repair Strategies Used by Elementary-Age Beginning Communicators With Autism

Abstract: This descriptive study extends previous studies on communication repairs by (a) involving elementary-age children With autism Who are prelinguistic to emergent one-Word communicators and (b) examining repair strategies in terms of the relationships betWeen the conventionality and functionality of communication forms and the type of breakdoWn. Communication initiations and repairs emitted by three students With autism Were observed in natural settings in Which communication breakdoWns Were intentionally introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Greenberg et al (2014) reported similar effects of a reinforcer delay during PECS instruction. Research has also suggested that individuals with ASD may substitute alternative responses when an initial mand form is not reinforced (Dincer & Erbas, 2010;Keen, 2005;Ohtake et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Greenberg et al (2014) reported similar effects of a reinforcer delay during PECS instruction. Research has also suggested that individuals with ASD may substitute alternative responses when an initial mand form is not reinforced (Dincer & Erbas, 2010;Keen, 2005;Ohtake et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding repair analysis, there are some studies on repair strategies that have been conducted in various contexts. For example in text-based communication, (e.g., Meredith & Stokoe, 2014;Tiara, 2018), students with autism (e.g., Ohtake, et al, 2005;Ohtake, Wehmeyer, Nakaya, Takahashi, & Yanagihara, 2011), and classroom (e.g., Cho & Larke, 2010;Rabab'ah, 2013). In the EFL context, some studies have been conducted, for example, Khodadady and Alifathabadi (2014) on repair in Iranian intermediate and advanced learners and Chalak and Karimi (2017) who examined turn-taking and repair strategies in Intermediate EFL learners.…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial amount of research on repair strategies used by verbal children with mild disabilities such as learning disabilities and mental retardation (only a small sample are cited here: Brinton & Fujiki, 1991;Gallagher & Darnton, 1978;Paul & Cohen, 1984;Scudder & Tremain, 1992), but few researchers have examined communication repair with children who have disabilities and limited expressive language (i.e., children who use fewer than 10 functional words or symbols spontaneously: Alexander, 1994;Halle, Carey, & Phillips, 1999;Meadan, Halle, Watkins, & Chadsey, 2006;Ohtake et al, 2005). Golinkoff (1986) found that 62% of communication episodes between young, typically developing children and their mothers were either negotiated or missed and only 38% were immediately successful.…”
mentioning
confidence: 98%